Recording and Accounting for Stakeholder Involvement in Systematic Reviews. (21st April 2015) - Saan, Marieke C.; Boeije, Hennie R.; Sattoe, Jane N. T.; Bal, Marjolijn I.; Missler, Marjolein; van Wesel, Floryt
Abstract Objectives The use of stakeholders in systematic reviews is increasingly valued, but their influence on the systematicity of the review is often unclear. The aim of this study was to describe some of the processes of involvement of stakeholders and to demonstrate a Tool for Recording and Accounting for Stakeholder Involvement (TRASI). Methods We demonstrate the TRASI in two worked examples. In one project, the reviewers collaborated with the end‐user and an expert during the literature search. In the other project, experts were consulted to generate keywords before searching the literature. Results In the first project, disagreements about keywords to identify studies for the research topic were solved by informal discussion. In the second project, difficulties arose in reaching agreement between experts and reviewers about the core construct and the meaningful keywords associated with it. Discussion The TRASI aids researchers to systematically and transparently account for the decisions taken. The TRASI supports information specialists and librarians to shape the search strategy to match the objectives of the review. Conclusions We propose the TRASI as a first step in resolving the challenges of detecting and reconstructing stakeholder influences. Potential new applications of the TRASI are discussed.